STRATEGI PERTUMBUHAN UNILEVER INDONESIA DALAM MEWUJUDKAN NILAI BERKELANJUTAN - Mubarok, Muhammad Husni (BISNIS, 2014)
This study aims to determine the strategy that used by Unilever Indonesia in realizing sustainable value so as to make Unilever Indonesia won the Capital Market Award for Best Listed Company. The results obtained showed that the strategy used by the company is refocused on the core business- the categories and products that drive profitability. In addition, the company also creates unbeatable value for their customers by tailoring quality and price of products to match their needs and preferences which consists of 26 brands in home and personal line-up and 14 brands in foods and refreshment. Sustainable value obtained through profitable volume growth, cost leverage, efficiency, innovation and marketing investment. For Unilever Indonesia, sustainability is central to their growth model. Indonesia is facing numerous social and environmental challenges, notably poverty, health, nutrition, resource sustainability, waste management and climate change. Profitable volume growth is driven by investment in innovation and brands to deliver products which 2 billion consumers use every day.